Radiotherapist’s View on the Role of Current Diagnostic Imaging in Pre-Radiation Preparation of Patients with Oligometastatic Disease for Conformal Radiotherapy - G. A. Panshin; N. V. Nudnov (Вестник рентгенологии и радиологии, 2024)
Diagnostic imaging of oligometastatic disease is a difficult task, since it requires determining the exact locoregional stage of the underlying disease and assessing the condition of the entire body in terms of possible diffuse spread of distant metastases, which presupposes a fairly frequent combination of various instrumental methods. In each specific case, a more accurate imaging method is chosen depending on the type of tumor, time of diagnosis, possible previously implemented stage of special antitumor treatment, as well as the individual risk of developing distant metastases, the most characteristic for this type of tumor process. Today, along with some diagnostic techniques that were previously constantly used in everyday practice, but are gradually losing their long-standing clinical application, such imaging methods as contrastenhanced computed tomography (CT), magnetic resonance imaging, as well as metabolic and specific receptor imaging, for example, CT combined with positron emission tomography with 18F-fluorodeoxyglucose, are most commonly performed, alone or in various combinations.